Deskripsi Morfologi Cacing Nipah Hitam (Namalycastis cf. terrestris) Asal Perairan Mangrove Sungai Kakap Kalimantan Barat - Chintia, Windy; Junardi, Junardi; Setyawati, Tri Rima (Jurnal Protobiont, 2020)
The black nypa worm (Namalycastis cf. terrestris) has not been widely used as an object of research, but its habitat in mangrove waters has been converted into agricultural land and tourist attractions. The purpose of the study was to obtain data on the distinguishing morphological characteristics of the black nypa worm Namalycastis sp. with other Namalycastis worms in the same habitat. Sampling was carried out 12 times for 3 months with a total sample of 68 worms consisting of 8 male individuals, 58 female individuals, and 2 juvenile individuals. The morphological characters measured included color, body length and weight, parapodia type and setae type which were then analyzed by t-test. Black nypa worm N. cf. terrestris is blackish green with a body length of 15,2-57 cm and a weight of 1,18-16,25 g. The prostomium has a pair of palps and the peristomium is equipped with 4 pairs of peristomial features and a pair of jaws. Parapodia of sub-biramous type without notopods. Setae N. cf. terrestris is golden brown with black acicular. Notopodial setae consist of sesquigomph spiniger, supra-neuroacicular setae consist of sesquigomph spiniger and heterogomph falsiger, and sub-neuroacicular setae which are heterogomph spiniger and heterogomph types. Black nypa worms are distinguished from other worms in the same genus and habitat only by body color.